Adaptive slip engagement control of a wet clutch in vehicle powertrain based on transmitted torque estimation. (15th May 2022) - Park, Jinrak; Choi, Seibum; Oh, Jiwon; Eo, Jeongsoo
Abstract: In the slip engagement of a wet clutch, the solenoid current-to-actuator piston pressure model (CPM) and the piston pressure-to-clutch transmitted torque model (PTM) are utilized for the clutch torque control. However, the CPM is changed depending on the amount of hysteresis, which is influenced by the hydraulic fluid temperature, and the PTM is changed due to the variation of the clutch friction coefficient and the touch point. Thus, the CPM and PTM should be adapted using the measurement information of the solenoid current and piston pressure for precise control of the clutch torque. In this study, an adaptive control method of the clutch torque in the slip engagement of a wet clutch is proposed which. The purpose of this study is to propose a clutch torque control method that does not use a piston pressure sensor when controlling the clutch torque of a wet clutch, so the suggested method does not require measurement of the piston pressure. In the method, the adaptation of the target piston pressure-to-clutch torque model (TPTM) is performed instead of the adaptation of the CPM and PTM, and the clutch torque is controlled using the compensated TPTM and nominal CPM instead of the compensated CPM and PTM. The proposed control method is verified experimentally by applying it to the slip engagement control of an engine clutch equipped in a production parallel hybrid vehicle. Highlights: Adaptive control of clutch torque in the slip engagement of a wet clutch. Slip control of a wet engine clutch in a parallel hybrid vehicle. The uncertainty on the solenoid current-to-clutch torque model. Wet clutch torque control without using the measurement of piston pressure. The adaptation of the target piston pressure-to-torque model.